2009
DOI: 10.1007/s10803-009-0890-5
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Driving Hazard Perception in Autism

Abstract: This study investigated whether individuals with ASD (autistic spectrum disorders) are able to identify driving hazards, given their difficulties processing social information, Klin et al. (Archives of General Psychiatry 59: 809-816, 2002). Twenty-three adult males with ASD and 21 comparison participants viewed 10 video clips containing driving hazards. In half of the clips the source of the hazard was a visible person (social); in the other half the source was a car (non-social). Participants with ASD identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 15 publications
1
66
1
Order By: Relevance
“…In addition to these core deficit areas, recent evidence suggests that adolescents and young adults with ASD have difficulty in learning safe driving skills [35]. In particular, compared with their typically developed peers, individuals with ASD demonstrated unsafe gaze patterns and higher levels of anxiety when operating a driving simulator [6], [7], responded slower during steering, identified fewer social hazards, and showed problematic multi-tasking ability [8], [9]. In the US, driving plays a critical role in everyday life and is essential for achieving adult independence.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these core deficit areas, recent evidence suggests that adolescents and young adults with ASD have difficulty in learning safe driving skills [35]. In particular, compared with their typically developed peers, individuals with ASD demonstrated unsafe gaze patterns and higher levels of anxiety when operating a driving simulator [6], [7], responded slower during steering, identified fewer social hazards, and showed problematic multi-tasking ability [8], [9]. In the US, driving plays a critical role in everyday life and is essential for achieving adult independence.…”
Section: Introductionmentioning
confidence: 99%
“…Studies with older children (around 5 years old) verified that while neurotypical children prefer hearing the voice of their mothers (social stimuli), children with an autism spectrum disorder (ASD) prefer hearing sounds that are not related to persons (non social stimuli) (Klin, 1991;. Similar conclusions were obtained by Mongillo et al (2008) and by Sheppard et al (2010). Attempting to explain this preference we can say that the social world appears to be too confusing and difficult to interpret for people with AS.…”
Section: Social Perceptionmentioning
confidence: 68%
“…The limited studies on driving in autism have reported that individuals with autism spectrum disorders perform worse than typically developed individuals. For example, the study of Sheppard and colleagues [28] found slower reaction time for reporting road hazards. They reasoned that the autism spectrum group had slower responses to hazards due to the complexity of judging the situation [9] or had difficulties in planning and producing movements to respond [12].…”
Section: Discussionmentioning
confidence: 99%
“…Sheppard and colleagues [28] examined detection of driving hazards and found that individuals on the autism spectrum were less accurate at reporting hazards arising from social activity and overall had slower reactions times in reporting both social and nonsocial events. Using a driving simulator, in a small study of 7 teenagers on the autism spectrum, it was reported that the ASD teenagers compared to TD were involved in a greater number of accidents such as off-road crashes, collisions and centre-line crossings [6].…”
Section: Introductionmentioning
confidence: 99%